Digitally enabled Cognitive Assessments in the Identification and Intervention for Dementia in Elderly Africans (IDEA) Study. (20th December 2022) - Urasa, Sarah; Boshe, Judith; Paddick, Stella‐Maria; Mushi, Declare
Abstract: Background: The Alzheimer's Disease International (ADI) reports that the Sub‐Saharan African population age 65+ will double in less than 25 years. That compares to high income countries whose doubling of this same age group took between 45‐115 years. ADI estimates 7.2% dementia prevalence rate in those 60+ years old. Incidence rates have been estimated to be lower, 4.1/1000 person years for those ages 60‐64, which is lower than that of high income countries, but these data come from only 5 studies involving 6 cohorts; total n=9, 494). The paucity of AD related research in Sub‐Saharian Africa is alarming given the aging demographics and requires an immediate and rapid response to drastically increase research efforts. The Tanzanian community‐based Identification and Intervention for Dementia in Elderly Africans (IDEA) Study is testing whether digitally enabled cognitive assessment methods will provide a framework from which to accelerate expanded AD related research in Sub‐Saharan African countries. Methods: The IDEA study was initiatied in 2014. It has been longitudinally assessing participants (n=437), age 65 years and older through biennial examinations that includes dementia related risk factors including Sociodemographics, cognitive tests, medical history, blood pressure, and grip strength. To this protocol, and in collaboration with the Davos Alzheimer's Collaborative Global Cohort Development program, will be added the collection of longitudinal AD‐related digital phenotypes through the use of a tablet in the clinic and through smartphone applications that can be self‐administered on a more frequent basis from the person's place of residence. Results: We will present demographic and clinical characterization of the cohort to date. We will further discuss both the challenges and the opportunities provided through the added digital phenotyping protocol. We will also examine how being part of the DAC international network of research will help accelerate expansion of research not just within Tanzania, but potentially to other Sub‐Saharan countries. Conclusions: Digital assessments offer a feasible and cost effective method for expanding dementia research in lower income regions who are facing near term realities of an aging population, but are still lagging in research that can inform healthcare preparedness.